Clinical Significance of Human Metapneumovirus in Refractory Status Epilepticus and Encephalitis: Case Report and Review of the Literature. (18th November 2015) - Vehapoglu, Aysel; Turel, Ozden; Uygur Sahin, Turkan; Kutlu, Nurettin Onur; Iscan, Akın
Abstract : Encephalitis is a complex neurological disease that is associated with significant morbidity and mortality, and the etiology of the disease is often not identified. Human metapneumovirus (hMPV) is a common cause of upper and lower respiratory tract infections in children. Few reports are available showing possible involvement of hMPV in development of neurologic complications. Here, we describe an infant, the youngest case in literature, with refractory status epilepticus and severe encephalitis in whom hMPV was detected in respiratory samples and review diagnostic workup of patient with encephalitis.